The book of requiems from the earliest ages to the present period - Burn, David 1974-; Bergé, Pieter 1967-; Chemotti, Antonio 1987- (Leuven University Press, 2023)
The present volume, the second in the series, treats settings composed between c. 1550 and c. 1650, a period in which the Requiem becomes a defining feature of the soundscape of Catholic death rituals.